Induction of macrophage colony-stimulating factor-dependent growth and differentiation after introduction of the murine c-fms gene into FDC-P1 cells. - Rohrschneider, L R (1989)
A system has been established for analyzing the functions of the c-fms/macrophage colony-stimulating factor (M-CSF) receptor gene product in hematopoietic growth and differentiation. The murine c-fms gene was introduced into the factor-dependent murine hematopoietic cell line FDC-P1 by retroviral infection, and conversion to M-CSF-dependent growth was assayed in agar cultures. Expression of the c-fms gene in FDC-P1 cells, which normally do not express this gene, resulted in the conversion of resultant FD(c-fms) cells to M-CSF-dependent growth. Stimulation of FD(c-fms) cells by M-CSF led to the formation of colonies of altered morphology and produced reversible morphological changes suggestive of myeloid differentiation. M-CSF also induced expression of mature myeloid surface marker proteins in the FD(c-fms) cells. Neither multi-CSF nor granulocyte-macrophage CSF induced similar phenotypic changes but remained able to stimulate the proliferation of undifferentiated FD(c-fms) cells. These results indicate that the c-fms gene was expressed functionally in FDC-P1 cells and transmitted signals for growth. Also, the interaction of M-CSF with the c-fms gene product generated an additional signal for myeloid differentiation but did not irreversibly commit FD(c-fms) cells to terminal differentiation. This system can be used for molecular analysis of the growth- and differentiation-promoting activities of the c-fms proto-oncogene.